Catalytic Oxidation of Benzaldehyde to Benzoic Acid with Keggin Polyoxometalate [(CH2)5NH2]3PW12O40 - Ding, Yuansheng; Lu, Fei-; Han, Xinbao- (Asian Journal of Chemistry, 2012)
The organic-inorganic hybrid catalyst [(CH2)5NH2]3PW12O40 was prepared by heteropoly acid and piperidine. The heteropoly acid was synthesized by sodium molybdate and sodium silicate and the piperidine was organic ligand. The proposed composition and structure of the catalyst were evidenced by FT-IR, XRD and TG-DTA. The results indicated that the heteropoly anions reserved their Keggin structure in the compound. Its catalytic performance was evaluated in the oxidation of benzaldehyde to benzoic acid. Various reaction parameters were changed to attain the optimal conditions. The optimal reaction conditions were found to be: n(catalyst):n(benzaldehyde) = 3.103 × 10-3:1; n(H2O2):n(benzaldehyde) = 4.0:1; reaction temperature 80 ºC; reaction time 4 h. The yield of benzoic acid achieved above 93 %, furthermore and the selectivity was 100 %.